2017
DOI: 10.1007/s10620-017-4782-9
|View full text |Cite
|
Sign up to set email alerts
|

Cirrhosis Is Associated with Increased Mortality in Patients with Diverticulitis: A Nationwide Cross-Sectional Study

Abstract: Presence of cirrhosis in patients hospitalized for diverticulitis is associated with an increased mortality rate. These are novel findings, and future clinical studies should focus on improving diverticulitis outcomes in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…According to these criteria, decompensation is defined by the presence of ascites, HE, variceal bleeding, or SBP. The ICD‐9‐CM codes used to identify those diagnoses are shown in Supporting Table and are comparable to those used in previous publications . We excluded patients less than 18 years of age (n = 266) and those discharged from the hospital during the month of December 2013 (n = 12,848) because of expected unavailability of 30‐day follow‐up data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to these criteria, decompensation is defined by the presence of ascites, HE, variceal bleeding, or SBP. The ICD‐9‐CM codes used to identify those diagnoses are shown in Supporting Table and are comparable to those used in previous publications . We excluded patients less than 18 years of age (n = 266) and those discharged from the hospital during the month of December 2013 (n = 12,848) because of expected unavailability of 30‐day follow‐up data.…”
Section: Methodsmentioning
confidence: 99%
“…The ICD-9-CM codes used to identify those diagnoses are shown in Supporting Table S1 and are comparable to those used in previous publications. (16,17) We excluded patients less than 18 years of age (n = 266) and those discharged from the hospital during the month of December 2013 (n = 12,848) because…”
Section: Study Populationmentioning
confidence: 99%
“…Previous studies have shown that the presence of DC independently increases mortality rates for other gastrointestinal diseases, including diverticulitis, peptic ulcer disease, Clostridium difficle infections, [25][26][27] along with non-gastrointestinal bacterial infections. The higher index admission mortality was heavily influenced by an increased mortality rate of 3.3% within those patients with decompensation.…”
Section: Discussionmentioning
confidence: 99%
“…The higher index admission mortality was heavily influenced by an increased mortality rate of 3.3% within those patients with decompensation. Previous studies have shown that the presence of DC independently increases mortality rates for other gastrointestinal diseases, including diverticulitis, peptic ulcer disease, Clostridium difficle infections, [25][26][27] along with non-gastrointestinal bacterial infections. 28 This appears to be the case for ABP as well.…”
Section: Discussionmentioning
confidence: 99%
“…Besides mortality, LOS, total hospital cost, and discharge disposition, which were variables in the dataset, all the other outcomes were identified using ICD-9-CM codes. The liver cirrhosis and the Baveno4 system codes have been extensively used and validated in the NIS [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%